Discomfort/Pain and Tissue Oxygenation at the Lower Limb During Circumferential Compression: Application to Soft Exoskeleton Design. (May 2020) - Kermavnar, Tjasa; O'Sullivan, Kevin J.; de Eyto, Adam; O'Sullivan, Leonard W.
Objective: To establish the relationship between circumferential compression on the lower limb during simulated ramp and staircase profile loading, and the resultant relationship with discomfort/pain and tissue oxygenation. Background: Excessive mechanical loading by exoskeletons on the body can lead to pressure-related soft tissue injury. Potential tissue damage is associated with objective oxygen deprivation and accompanied by subjective perception of pain and discomfort. Method: Three widths of pneumatic cuffs were inflated at the dominant thigh and calf of healthy participants using two inflation patterns (ramp and staircase), using a computer-controlled pneumatic rig. Participants rated discomfort on an electronic visual analog scale and deep tissue oxygenation was monitored using near infrared spectroscopy. Results: Circumferential compression with pneumatic cuffs triggered discomfort and pain at lower pressures at the thigh, with wider cuffs, and with a ramp inflation pattern. Staircase profile compression caused an increase in deep tissue oxygenation, whereas the ramp profile compression decreased it. Conclusion: Discomfort and pain during circumferential compression at the lower limb is related to the width of pneumatic cuffs, the inflation pattern, and the volume of soft tissue at the assessment site. The occurrence of pain is also possibly related to the decrease in deep tissue oxygenation during compression. Application: Our findings can be used to inform safe and comfortable design of soft exoskeletons to avoid discomfort and possible soft tissue injury.